Penerapan Pembelajaran Berbasis Proyek Untuk Meningkatkan Kemampuan Membaca Siswa Sekolah Dasar - Alvina Agustin; Ibnu Muthi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study have a purpose analyze the implementation of project-based learning in increased resilience elementary school students' reading skills, particularly in Indonesian language learning for third-grade students. The method used is a literature review, which collects and examines various relevant studies and sources. The results of the review show that project-based learning can provide more interactive and contextual learning experiences for students, leading to increased motivation and interest in reading. Additionally, this method promotes the development of critical thinking skills, creativity, and collaboration among students. By integrating projects into the learning process, students become more actively engaged and have the opportunity to apply their knowledge in real-world situations. Overall, the implementation of project-based learning has proven effective in enhancing third-grade students' reading skills in Indonesian language learning. This study offers practical implications for educators in designing and implementing innovative and effective teaching strategies, and underscores the importance of more active and participatory learning approaches in elementary education.